About the turbulent scale dependent response of reflexed airfoils - Delnero, Juan Sebastián (2005)
Boundary layer wind tunnel experiments have been conducted to explore differences in the aerodynamic behavior of two autostable or reflexed airfoils, with different positive camber submitted to three different incoming flows with the same mean velocity but with different turbulence characteristics. The variations of lift and drag coefficients due to the path of turbulent structures with different scales are presented. The experiments were performed at a mean speed of 10 m/sec, corresponding to a Reynolds Number of 205000.